Autism spectrum disorder in a community-based sample with neurodevelopmental problems in Lagos, Nigeria - Yewande O. Oshodi; Andrew T. Olagunju; Motunrayo A. Oyelohunnu; Elizabeth A. Campbell; Charles S. Umeh; Olatunji F. Aina; Wellington Oyibo; Folusho E.A. Lesi; Joseph D. Adeyemi (AOSIS, 2017)
Autism Spectrum Disorder (ASD) is a globally prevalent neurodevelopmental disorder for which early diagnosis and intervention is the mainstay of management. In the African continent, limited data is available regarding the non-clinic based samples. Lack of information available to caregivers and inadequate skilled manpower often limit early detection and access to the few available though under resourced services in the community. Community based screening can be an important drive to create awareness and improve information dissemination regarding services available for those living with this disorder. This is a descriptive cross-sectional study utilizing data obtained from participants of a community-based autism screening exercise. The surveillance exercise was part of the annual Orange Ribbon initiative for autism awareness and screening held in 2014. Data was obtained from 85 participants involved in the Autism Surveillance screening exercise within the Lagos community. Community public service radio announcements state wide and word of mouth were used to invite and enroll eligible participants to the screening and consultation exercise. A second stage screening and a brief sociodemographic questionnaire followed by a third stage clinical interview and evaluation using the Diagnostic and Statistical Manual of Mental Disorders - 5 Edition (DSM 5) were used. Appropriate consultation and referrals to services in the community were given. Participants had a mean age of 7.53 years (SD 4.35). Twenty-nine (34.5%) met the diagnosis of ASD. Other diagnosis included attention deficit hyperactivity disorder (ADHD), language and speech disorder, intellectual disability (8.3%) and learning disorders (9.5%). Main health concerns to caregivers were poor language development in all (100%), of which 11 (40.7%) were non-verbal; gaze avoidance was seen in 14 (48.3%) and challenging behavior in 12 (42.9%). Comorbidities included seizure disorders (3.4%) and ADHD (6.9%). Persons with autism had history of ASD behavior more often when compared to the other neurodevelopmental disorders and these findings were statistically significant. Referrals were given to caregivers to engage in services within the community. As seen in this study, community understanding of ASD is poor in such locations, in which many persons with other neurodevelopmental disorders are often presented as having autism. Caregivers in the study location are distressed by many symptoms associated with autism and their comorbid conditions. Currently there is an evident role for frequent large scale community based screening and autism awareness exercises possibly using inter-sectoral collaboration as a strategy.